Kedudukan Badan Pertanahan Nasional Sebagai Mediator Dalam Penyelesaian Sengketa Pertanahan - Rasmawati, Irma; Laturette, Adonia Ivone; Radjawane, Pieter (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This study discusses the position of the National Land Agency as a Mediator in Land Dispute Resolution.Purposes of the Research: To find out what factors are faced by the Ambon City National Defense Agency as a Mediator in Land Dispute Resolution, the position of the National Land Agency as a mediator for the parties in resolving land disputes and to find out the position of the National Land Agency as a Mediator to the Parties in Settlement. Land Dispute. Methods of the Research: This study uses a normative juridical method using a statutory approach, a conceptual approach, and a case approach.Results of the Research: Based on the results of research that the Ambon City National Land Agency (BPN) Office can act as a mediator in land dispute resolution, but sometimes in the settlement there are obstacles which are factors or circumstances that limit, hinder, or prevent the achievement of targets faced between another: That the court's decision attached to its ruling does not mention the cancellation of the Certificate of Ownership (SHM), and there are also disputes that are not within the authority of the Ambon City BPN to settle. The position of BPN as a non-ministerial government agency tasked with implementing and developing land administration. The conclusions and suggestions are: To overcome obstacles in the resolution of land disputes, it is very necessary to have a good administrative device, then the position of the National Land Agency (BPN) acts as a mediator to those in dispute to resolve land disputes/conflicts to the parties to the dispute, the role of the BPN as a mediator. Mediator, then BPN needs to improve Human Resources (HR) and socialize its position related to land settlement.